Allometry and Sexual Dimorphism in the Human Pelvis. Issue 4 (April 2017) - Fischer, Barbara; Mitteroecker, Philipp
ABSTRACT: Sexual dimorphism in the human pelvis has evolved in response to several jointly acting selection regimes that result from the pelvis' multiple roles in locomotion and childbirth, among others. Because human males are, on average, taller than females, some aspects of sexual dimorphism in pelvis shape might result from allometry, the association between stature and pelvis shape across individuals. In this study, they aimed to disentangle and quantify the two components contributing to pelvic sex differences: the allometric component, which emerges as a consequence of dimorphism in stature, and the remaining non‐allometric sexual dimorphism component. A geometric morphometric analysis of a dense set of 3D landmarks, measured on 99 female and male adult individuals was conducted. While pelvis size was similar in both sexes, the average differences in pelvis shape reflected the well‐documented pattern of sexual dimorphism. There was almost no overlap between females and males in shape space. Their analysis showed that pelvis size and shape were similarly associated with stature in both sexes. It was found that dimorphism in the height‐to‐width ratio of the pelvis and in the orientation of the iliac blades was largely allometric, whereas dimorphism in the subpubic angle and the relative size and distance of the acetabula was largely non‐allometric. It was concluded that, in contrast to the overall pelvic proportions, sexual dimorphism in the birth‐relevant pelvic dimensions was mainly of non‐allometric origin and was presumably mediated via steroid hormone secretion during puberty. Anat Rec, 300:698–705, 2017. © 2017 Wiley Periodicals, Inc.